2014
DOI: 10.1016/j.nut.2014.02.027
|View full text |Cite
|
Sign up to set email alerts
|

An ethanolic extract of Artemisia dracunculus L. regulates gene expression of ubiquitin–proteasome system enzymes in skeletal muscle: Potential role in the treatment of sarcopenic obesity

Abstract: Objective Obesity is linked to insulin resistance, a primary component of metabolic syndrome and type 2 diabetes. The problem of obesity-related insulin resistance is compounded when age-related skeletal muscle loss, called sarcopenia, occurs with obesity. Skeletal muscle loss results from elevated levels of protein degradation and prevention of obesity-related sarcopenic muscle loss will depend on strategies that target pathways involved in protein degradation. An extract from Artemisia dracunculus, termed PM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 43 publications
0
3
0
2
Order By: Relevance
“…Muscle atrophy induced by an HFD is explained through various mechanisms, including an imbalance between protein synthesis and degradation. The ubiquitin proteasome system catalyzes the degradation of most cellular proteins 46 and is one of the major pathways regulating muscle protein degradation; this system plays a central role in controlling muscle size 1 . Atrogin1 and MuRF1 are two E3 ubiquitin ligases that are important regulators of ubiquitin-mediated protein degradation in skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Muscle atrophy induced by an HFD is explained through various mechanisms, including an imbalance between protein synthesis and degradation. The ubiquitin proteasome system catalyzes the degradation of most cellular proteins 46 and is one of the major pathways regulating muscle protein degradation; this system plays a central role in controlling muscle size 1 . Atrogin1 and MuRF1 are two E3 ubiquitin ligases that are important regulators of ubiquitin-mediated protein degradation in skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%
“…AMPK activates the autophagy-initiating serine/threonine protein kinase ULK1 (ULK1), whereas the PI3K/Akt/mTOR axis acts as a negative regulator of autophagy by blocking the activation of ULK1. Several studies have shown a clear effect of defective autophagy on muscle under conditions of obesity, where reduced activation of AMPK and increased induction of AKT and mTOR were found ( Turpin et al, 2009 ; Kirk-Ballard et al, 2014 ; Barlow and Thomas, 2015 ; Ryu et al, 2020 ). However, the interplay between overweight and autophagy and its implication on muscle wasting are far from fully understood.…”
Section: Predictive Biomarkers Of Sarcopenic Dependencementioning
confidence: 99%
“…As a result of its rich content, it is known that tarragon plant has anti-inflammatory, antidiabetic, antiseptic activities and is also effective in insomnia, allergic rashes and dermatological treatments. In the studies conducted, it has been stated that the extracts of the plant reduce inflammation in the human skeletal muscular system, improve insulin sensitivity and have a strong healing effect in the treatment of muscle loss and obesity due to old age (Obolskiy et al, 2011;Kirk-Ballard et al, 2014;Vandanmagsar et al, 2014;Karaman and Sezgin, 2022).…”
Section: Introductionmentioning
confidence: 99%